One-pot crystalline ZnO nanorod growth in mineralizing peptide gels - Anjia, Luona (RSC Adv, 2012)
A new biomimetic approach for the one-pot synthesis of ZnO nanorods at neutral pH and room temperature is introduced; self-assembly of the ZnO-mineralzing peptides (CN111, PAGLQVGFAVEV-GGGSC) with Zn ions as bundles of nanofibers in the gel form leads to the growth of ZnO nanorod (NRD) inside the gel. This new nanomaterial synthesis may open a new strategy by using the catalytic peptide gels as nanomaterial reactors.